In a fair gambler's ruin problem, where the gambler starts with k dollars, wins \$1 with probability 1/2 and loses \$1 with probability 1/2, and stops when he/she reaches \$n or \$0.

In the solution (from Dobrow's Introduction to Stochastic Processes with R), they let $p_k$ be defined as the probability of reaching \$n with \$k in one's inventory. Then they use the fact that $p_k - p_{k-1} = p_{k-1} - p_{k-2} = ... = p_1 - p_0 = p_1$.

Intuitively this means the probability of reaching \$n with \$k minus the probability of reaching \$n with \$k-1 is equivalent to the probability of reaching \$n with only \$1.

Is there an intuitive reason why this is the case?


Regarding an "intuitive" reason for this relation, note that winning or losing a dollar has an equal chance and is independent of how much your currently have. Thus, the change in probability of winning or losing when starting off with \$$1$ more is independent of what your starting value is. Note that if $q_k = 1 - p_k$ is the probability of losing when starting with \$$k$, then plugging $p_k = 1 - q_k$ in gives that

$$q_{k-1} - q_k = q_{k-2} - q_{k - 1} = \ldots = q_1 - q_2 = q_0 - q_1 \tag{1}\label{eq1}$$

Note you can reverse all the elements by multiplying by $-1$ to give the exact same relationship as with $p_k$.

Regarding how to get the relationship, this answer originally started with that, as the answer by John Doe states, the difference relation for reaching \$n starting with \$i is given by

$$p_i = \frac{1}{2}p_{i - 1} + \frac{1}{2}p_{i + 1} \tag{2}\label{eq2}$$

based on the probabilities of either winning or losing the first time. Summing \eqref{eq2} for $i$ from $1$ to $k - 1$ gives

$$\sum_{i=1}^{k-1} p_i = \frac{1}{2}\sum_{i=1}^{k-1} p_{i - 1} + \frac{1}{2}\sum_{i=1}^{k-1} p_{i + 1} \tag{3}\label{eq3}$$

Having the summations only include the common terms on both sides gives

$$p_1 + \sum_{i=2}^{k - 2} p_i + p_{k-1} = \frac{1}{2}p_0 + \frac{1}{2}p_1 + \frac{1}{2}\sum_{i=2}^{k - 2} p_i + \frac{1}{2}\sum_{i=2}^{k - 2} p_i + \frac{1}{2}p_{k-1} + \frac{1}{2}p_k \tag{4}\label{eq4}$$

Since the summation parts on both sides up to the same thing, they can be removed. Thus, after moving the $p_0$ and $p_1$ terms to the LHS and the $p_{k-1}$ term on the left to the RHS, \eqref{eq4} becomes

$$\frac{1}{2}p_1 - \frac{1}{2}p_0 = \frac{1}{2}p_k - \frac{1}{2}p_{k-1} \tag{5}\label{eq5}$$

Multiplying both sides by $2$, then varying $k$ down, gives the relations you stated are used in the solution. However, it's generally simpler & easier to just manipulate \eqref{eq2} to get that $p_{i+1} - p_{i} = p_{i} - p_{i-1}$, like John Doe's answer states.


The probability of reaching \$$n$ starting with \$$k$ can be split up by what possible first steps you can take - you either lose the first toss or win, each with probability $1/2$. If you win, you have \$$(k+1)$, so the probability of reaching \$$n$ from here is $p_{k+1}$. If instead, you lose the first toss, then its \$$p_{k-1}$. Then use the Law of Total Probability $P(X)=\sum_n P(X|Y_n)P(Y_n)$ where $Y_n$ is a partition of the sample space. In this case, $Y_1=\{\text{lose toss}\}$, and $Y_2=\{\text{win toss}\}$. Then you get

$$p_k=\frac12(p_{k-1}+p_{k+1})$$ Rearranging this gives $$2p_k=p_{k-1}+p_{k+1}\\p_k-p_{k-1}=p_{k+1}-p_k$$ as required, and iterating it multiple times gets to $p_1-p_0$, and of course, $p_0=0$.


Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.